An Innovative Framework to Improve Teratogenic Medication Risk Counseling. (9th May 2017) - Shroff, Swati; McNeil, Melissa; Borrero, Sonya
Abstract : Health care providers in the Veterans Affairs system are caring for a growing number of women of childbearing age. Prior research shows that a significant number of women veterans are prescribed category D or X teratogenic medications. However, the majority do not receive teratogenic risk or contraceptive counseling. In order to improve teratogenic medication prescribing practices at the Veterans Affairs Pittsburgh Healthcare System, we developed a framework called TARCC to guide primary care providers through appropriate teratogenic risk counseling. The components of TARCC are teratogen (Are you prescribing a potential teratogen?), alternative (Did you consider a nonteratogenic alternative?), risks (Did you discuss the risks of the medication?), contraception (Did you discuss contraception?), and chart (Did you chart your discussion?). We incorporated TARCC into an electronic health record reminder. Additional probes, educational tools, and options to place consults and orders are included within the reminder. The Teratogen Pharmacy E‐consult prompts a pharmacist to electronically review a patient's medications and provide recommendations regarding potential alternatives and discussions of risks and benefits. This article describes the development and implementation of the TARCC framework in a clinical reminder.